Analisis Keterlambatan Waktu Pengerjaan Proyek Perbaikan Rumah di Sommerset GF Citraland, Surabaya Menggunakan Metode CPM pada CV Sinar Berkah Utama, Surabaya Jawa Timur - Risqi Firmansyah Abdulah; Wiwik Handayani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Sinar Berkah Utama is a construction service provider company. However, with the experience and good name that CV. Sinar Berkah Utama, this company is still experiencing delays in project completion. So time management analysis was carried out in the completion of home improvement project work in Sommerset GF, Citraland, Surabaya using the CPM (Critical Path Method) method. The purpose of this study was to find out the practical benefits of time management in the completion of home improvement projects in Sommerset GF, Citraland, Surabaya by CV. Sinar Berkah Utama. This study use a quantitative descriptive approach. Descriptive quantitative is a research that has the aim to describe a phenomenon, events, symptoms, and events that factually, systematically, and accurately. Using the CPM (Critical Path Method) method, the authors found the critical path for this project was in the preparation of work (A) - Dismantling of glass and removing the AC installation (B) - walls and beams for room widening (D) - Structural and concrete (F) - Wall work (G) - Roof work (H) - Plafound work (I) - Electrical installation (M) - AC and interior installation (N) - removal from cluster (O). From the existing critical path, the author crashes by increasing working hours (overtime). Based on the above calculations, it can be seen that the duration of the work on the Sommerset GF home improvement project by CV. Sinar Berkah Utama, the project was reduced by 13 working days from the original 102 working days to 89 working days. Keywords: Project, CV. Sinar Berkah Utama, CPM, Duration